2020
DOI: 10.1016/j.heliyon.2020.e03301
|View full text |Cite
|
Sign up to set email alerts
|

Modification of TRPV4 activity by acetaminophen

Abstract: N-Acetyl-p-aminophenol (APAP/acetaminophen) is a widely used analgesic/antipyretic with weaker inhibitory effects on cyclooxygenase compared to those of non-steroidal anti-inflammatory drugs. The effect of APAP is mediated by its metabolites, N-arachidonoyl-phenolamine and N-acetyl-p-benzoquinone imine, which activate transient receptor potential (TRP) channels, including TRP vanilloid 1 (TRPV1) and TRP ankyrin 1 (TRPA1) or cannabinoid receptor type 1. However, the exact molecular mechanism underlying the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…have revealed that the Ca2þ channel activity of TRPV4 is inhibited by paracetamol. 146 The effects of paracetamol on TRPV4 differed from the action on TRPV1 and TRPA1 reported previously. Firstly, paracetamol metabolites are unlikely to be involved in these effects,…”
Section: Paracetamol and Trp Channelsmentioning
confidence: 71%
See 4 more Smart Citations
“…have revealed that the Ca2þ channel activity of TRPV4 is inhibited by paracetamol. 146 The effects of paracetamol on TRPV4 differed from the action on TRPV1 and TRPA1 reported previously. Firstly, paracetamol metabolites are unlikely to be involved in these effects,…”
Section: Paracetamol and Trp Channelsmentioning
confidence: 71%
“…were activated by paracetamol in vivo. 146 However, the molecular mechanism of paracetamol activity on the Ca2þ channel activity of TRPV4 is complex, as it is not known whether it works outside or inside the cell membrane of theTRPV4 Ca2þ channel. Finally, inhibition of Ca2þ entry into cells via TRPV4 may also contribute to the clinical effects induced by paracetamol, which has not been reported previously as a paracetamol target.…”
Section: Paracetamol and Trp Channelsmentioning
confidence: 99%
See 3 more Smart Citations